Influence of Photon Beam and Motor Vibrations on At-Wavelength X-Ray Speckle Scanning Metrology - Tian, Naxi; Jiang, Hui; Xue, Lian; Xie, Jianan (Frontiers in Physics, 2022)
Speckle scanning metrology is an effective tool to determine the X-ray wave front error in synchrotron radiation. By measuring wave front radii of curvature, X-ray optics can be high-precision aligned and adaptive optics can be used for compensating these wave front errors to pursue an aberration-free wave front. Photon beam and motor vibrations are the major limitations in characterizing the beam performances. An analytical model is presented in this article to reveal the influences of photon beams and motor vibrations on the measurements of the wave front radii of curvature. It is worth noting that the influence of low-frequency vibration is oscillatory and thus the selection of sampling frequency is strongly related. The experimental results verify the model and reveal the main dependency of the experimental deviations on the amplitude and frequency of vibrations.